Social values, societal entrepreneurship attitudes and entrepreneurial intention of young people in the Finnish welfare state - RANTANEN, Teemu; TOIKKO, Timo (Economics and Business Review, 2025)
The article is focused on Finnish youth’s social values, societal entrepreneurship attitudes and entrepreneurial intention. The study addresses how the relationship between social values and societal entrepreneurship attitudes becomes visible among Finnish youngpeople. What is the relationship between social values and entrepreneurial intention? What is the relationship between societal entrepreneurship attitudes and entrepreneurial intention? We also analyze the relationship between diff erent social values of the Finnish welfare state. Survey data (N = 873) were gathered in electronic format from secondary and vocational schools in the Helsinki–Uusimaa region, and questions were based on a multiple-choice Likert scale. The analysis was undertaken using statistical methods. We found that Finnish young people consider entrepreneurship first and foremost a pragmatic career option, which is not supported by ideological arguments or assumptions. On the other hand, the connection between social values and entrepreneurial orientation remains largely at the level of attitudes.